Choisyaternatine, a New Alkaloid Isolated from Choisya ternata - Wahab, Ikarastika Rahayu Abdul; Wong, Nikki Siu Hai; Boylan, Fabio (Planta Medica, 2012)
One novel compound was isolated from the hexane extract of Choisya ternata Kunth. leaves, choisyaternatine (1), together with the known compounds tecleamaniensine A (2), lup-20(29)-en-3β-ol (lupeol) (3), lup-20(29)-en-3β,24-diol (4), β-sitosterol glucoside (5), and skimmianine (6), plus the following known compounds from the dichloromethane extract, choisyine (7) and 6-methoxy-7,8-methylenedioxycoumarin (8). Compounds 2–5 are reported for the first time in this species. The structures of isolated compounds were elucidated by extensive spectroscopic analyses and comparison with previously reported spectroscopic data. The structure of choisyaternatine was further confirmed based on X-ray data analysis.
Keywords: Choisya ternata; Rutaceae; choisyaternatine; alkaloids; triterpenes